Integration of GPS and GSM for the Weather Monitoring System - K.R. Trivedi; Dhiren P Mistry (Institute of Advanced Engineering and Science, 2012)
This paper describes the design, implementation and results of Weather monitoring system. This System provides solution for Weather monitoring of remote places. The system consists: GPS receiver, GSM modem and microcontroller board for the purpose of weather monitoring. The system basically sense the weather parameter like temperature,humidity,Carbion Monoxide Level, level of Alcohol Gases , Light level of the Area in which system is located. By using a GPS technology, track the location of the area in terms of latitude and longitude. All the data of Sensors and GPS data can be accessed by using GSM Technology with the help of GSM modem. It can send the data to the user in the form of SMS in case of on request. The system can also be configured to transit the data on critical or threshold level of parameter is detected or at preset intervals to the user.